14. The Violin in L'histoire Du Soldat - A Metaphor of the Soul - Vișenescu Oana Iuliana (Sciendo, 2021)
From 1909, Stravinsky manifested a keen interest in composing theatre music, as proves the many and various dedicated scores. Almost all of his large works, from the ballet The Firebird (1909-10) to the one-act opera buffa Mavra (1921-22), are written for the stage. Stravinsky thus worked most of the time with scenic presentations, with questions on movement, dance, gestures or scenic tableaus. He develops a particular theatrical instinct: his works have a good scenic orientation, and the correlation with modernism and the new currents in theatre aesthetics is more than obvious. Critics have already analysed and discussed the parallels with such contemporary theatrical concepts as by Bertold Brecht (1898-1956) or Vsevolod Meyerhold (1874-1940). After three great ballets, whose new conception by Stravinsky and Sergei Diaghilev (1872-1929) brought about a fundamental revolution in dance aesthetics, the composer crystallises his notion of incidental music. The aesthetics of L'Histoire du soldat, a work "to be read, played and danced", is opposed to that of Richard Wagner (1813-83) and his Gesamtkunstwerk (a work blending various arts, a total work of art): a new artistic idea, frozen in gesture and movement, compressed, finding its concentrated expression. Stravinsky establishes a brilliant draft of the issues of Opera, to which he would from now on dedicate himself. Stravinsky's theatre music reveals a tendency to introduce new concepts in the works written between Sacre du printemps and Pulcinella. A quick look at his stage works before and after L'histoire is necessary in order to fit it in his artistic view.